Influence of Gut Microbiota and Nutritional Status on the Evolution of Chronic Inflammatory Bowel Diseases and its Association with Preeclampsia - Alvarez, Gabriela Melgar; Flórez, Fabián Andrés Urrea; García, Alejandra Macías (Journal of Neonatal Surgery, 2025)
Chronic inflammatory bowel diseases (IBD), such as Crohn's disease and ulcerative colitis, have been linked to alterations in the gut microbiota and nutritional status of the individual. Gut dysbiosis and malnutrition can aggravate intestinal inflammation and complicate other physiological states such as pregnancy. Preeclampsia, a multisystemic complication of pregnancy, has also been associated with alterations in the microbiota and nutritional deficiencies. This article explores the interrelationship between gut microbiota, nutritional status, IBD, and its possible pathophysiological link with preeclampsia. Recent studies (2019-2024) were reviewed to identify common mechanisms and establish therapeutic recommendations. The findings suggest that the maintenance of an eubiotic microbiota and optimal nutritional status could represent prevention and management strategies for both IBD and preeclampsia